2020
DOI: 10.1021/jacs.0c04284
|View full text |Cite
|
Sign up to set email alerts
|

Detection of OG:A Lesion Mispairs by MutY Relies on a Single His Residue and the 2-Amino Group of 8-Oxoguanine

Abstract: MutY glycosylase excises adenines misincorporated opposite the oxidatively damaged lesion, 8-oxo-7,8dihydroguanine (OG), to initiate base excision repair and prevent G to T transversion mutations. Successful repair requires MutY recognition of the OG:A mispair amidst highly abundant and structurally similar undamaged DNA base pairs. Herein we use a combination of in vitro and bacterial cell repair assays with single-molecule fluorescence microscopy to demonstrate that both a Cterminal domain histidine residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…More recent experiments using higher sampling rates [58] confirmed that the main mode of diffusion for OGG1 on DNA is helical sliding. Single molecule studies on the bacterial Nth, Nei, Fpg, and MutY have recently showed that these DNA glycosylases involved in the repair of oxidative DNA damage also scan for their cognate lesions at rates consistent with random rotational diffusion along the DNA backbone [59,60]. Interestingly, the values of activation energy obtained using instantaneous diffusion rate results are consistent with OGG1 examining flipped-out bases one by one.…”
Section: -Oxog Recognition By Ogg1 On Naked Dnamentioning
confidence: 65%
“…More recent experiments using higher sampling rates [58] confirmed that the main mode of diffusion for OGG1 on DNA is helical sliding. Single molecule studies on the bacterial Nth, Nei, Fpg, and MutY have recently showed that these DNA glycosylases involved in the repair of oxidative DNA damage also scan for their cognate lesions at rates consistent with random rotational diffusion along the DNA backbone [59,60]. Interestingly, the values of activation energy obtained using instantaneous diffusion rate results are consistent with OGG1 examining flipped-out bases one by one.…”
Section: -Oxog Recognition By Ogg1 On Naked Dnamentioning
confidence: 65%
“…We recently showed that MutY utilizes the major groove 2-amino group of OG as a key detection and recognition feature of OG:A mismatches. 26,27 The results presented in this work demonstrate the fidelity of MutY for binding and excising only A, or structures closely resembling A. The fact that T:A or OG:C bps do not present a 2-amino group in the major groove of DNA allows MutY to rapidly bypass these bps and avoid aberrant excision.…”
Section: T H I S C O N T E N T Imentioning
confidence: 66%
“…In previous studies directed at understanding the structural requirements of OG on lesion recognition and catalysis, we showed that MutY relies on the exocyclic 2-amino group of OG to identify and distinguish this mispair from structurally similar T:A bps. 26,27 We also showed that OG binding induces conformational changes that influence A excision. 26,28 Herein, we use structure−activity relationships (SARs) to identify the structural features of A that influence OG:A recognition, verification, base excision, and overall cellular repair.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Adenine excision is known to occur within the N-terminal catalytic domain of MUTYH, while 8-oxoG recognition resides primarily in a C-terminal 8-oxoG recognition domain ( 14–16 ). In a recent study, using single molecule microscopy, in vitro glycosylase and cellular repair assays, the Lee and David laboratories showed that Escherichia coli MutY detects 8-oxoG:A mispairs via the unique major groove positioning of the 2-amino group 8-oxoG using a conserved histidine residue within an ‘FSH’ loop of the C-terminal 8-oxoG recognition domain ( 13 ). Notably, identification of this distinct chemical signal of 8-oxoG:A mismatches would be anticipated to be further complicated in eukaryotic genomes, where the damaged mismatch can be sequestered within chromatin.…”
Section: Introductionmentioning
confidence: 99%